2016
DOI: 10.1186/s12944-016-0306-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of Meratrim for weight management: a randomized, double-blind, placebo-controlled study in healthy overweight human subjects

Abstract: BackgroundMeratrim is a blend of two plant extracts obtained from Sphaeranthus indicus flower heads and Garcinia mangostana fruit rinds. Previous studies have demonstrated that Meratrim is effective for weight management in obese individuals. The objective of this study was to assess the efficacy and tolerability of Meratrim in managing body weight in healthy overweight subjects.MethodsSixty participants with a mean BMI of 28.3 kg/m2 were randomized into two groups receiving either 400 mg of Meratrim twice dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 27 publications
4
35
0
1
Order By: Relevance
“…However, it is well documented that gastric bypass surgery promotes weight loss and improve the following body weight maintenance and that it is largely mediated by profound postprandial changes in gastrointestinal hormone secretion associated with enhanced satiety/reduced hunger . Biological markers of appetite were assessed in five of the included studies, but differences between the intervention and the control groups were only reported in three of these . After a single exposure to the foods, the orexigenic hormone ghrelin was found to be lower, and the anorexigenic hormones GLP‐1 and PYY were found to be higher in the intervention groups compared with the control groups in line with previous findings on associations between a number of gastrointestinal hormones and appetite .…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…However, it is well documented that gastric bypass surgery promotes weight loss and improve the following body weight maintenance and that it is largely mediated by profound postprandial changes in gastrointestinal hormone secretion associated with enhanced satiety/reduced hunger . Biological markers of appetite were assessed in five of the included studies, but differences between the intervention and the control groups were only reported in three of these . After a single exposure to the foods, the orexigenic hormone ghrelin was found to be lower, and the anorexigenic hormones GLP‐1 and PYY were found to be higher in the intervention groups compared with the control groups in line with previous findings on associations between a number of gastrointestinal hormones and appetite .…”
Section: Discussionsupporting
confidence: 77%
“…Hence, unchanged appetite after diet‐induced weight loss should not necessarily be interpreted as a lack of sustained effect on appetite. This was found by Kudiganti et al who reported maintained level of appetite in the intervention group despite greater weight loss compared with the control group while the control group showed an increased appetite after the weight loss, as could be expected after diet‐induced weight loss (Table ) . In the study by Rondanelli et al, the effect on appetite may have been too weak to affect body weight, possibly explaining why similar weight losses were found in both groups.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations